2021
DOI: 10.1155/2021/6330828
|View full text |Cite
|
Sign up to set email alerts
|

ACAMA: Deep Learning-Based Detection and Classification of Android Malware Using API-Based Features

Abstract: As a great number of IoT and mobile devices are used in our daily lives, the security of mobile devices is being important than ever. If mobile devices which play a key role in connecting devices are exploited by malware to perform malicious behaviors, this can cause serious damage to other devices as well. Hence, a huge research effort has been put forward to prevent such situation. Among them, many studies attempted to detect malware based on APIs used in malware. In general, they showed the high accuracy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, DBNs have been utilized in extracting invariant representations of malware behavior, as evidenced by [16], exposing the adaptability of DBNs to capture complex malware behavior patterns. Moreover, DBNs have been demonstrated to be instrumental in Android malware detection with studies by [44,45] which demonstrated the efficacy of DBNs in processing static features and enhancing detection accuracy. The application of DBNs in cybersecurity extends to the detection of intrusions and malware, as highlighted by [46], emphasizing the broad utility of DBNs in safeguarding systems against cyber threats.…”
Section: Related Studiesmentioning
confidence: 99%
“…Additionally, DBNs have been utilized in extracting invariant representations of malware behavior, as evidenced by [16], exposing the adaptability of DBNs to capture complex malware behavior patterns. Moreover, DBNs have been demonstrated to be instrumental in Android malware detection with studies by [44,45] which demonstrated the efficacy of DBNs in processing static features and enhancing detection accuracy. The application of DBNs in cybersecurity extends to the detection of intrusions and malware, as highlighted by [46], emphasizing the broad utility of DBNs in safeguarding systems against cyber threats.…”
Section: Related Studiesmentioning
confidence: 99%
“…Abubaker et al [4] gives framework that uses feature selection based on an ensemble extra tree classifier approach and a machine learning classifier to examine the behavior of malware apps by evaluating permissions. When it comes to detecting and classifying malware, a method has been presented [5]. DL-droid is a deep learning system that can detect malicious android apps by methodical input generation and dynamic analysis [6].…”
Section: Literature Reviewmentioning
confidence: 99%